An Imidazoline–Aminophenol (IAP) Nickel Catalyst: Structure and Catalytic Activity in the Enantioselective 1, 4‐Addition of 3′‐Indolyl‐3‐Oxindoles to Nitroethylene. Issue 9 (12th February 2014) - Awata, Atsuko; Wasai, Makiko; Masu, Hyuma; Kado, Sayaka; Arai, Takayoshi
Abstract The structure of a nickel complex of imidazoline–aminophenol (IAP) prepared from IAP with Ni(OAc)2 was elucidated as cis‐bis(imidazolineaminophenoxide) [Ni(IAP)2]. The [Ni(IAP)2] complex smoothly promoted catalytic asymmetric 1, 4‐addition of 3′‐indolyl‐3‐oxindole to nitroethylene to provide chiral mixed 3, 3′‐bisindoles with high enantioselectivities. Mechanistic studies using ESI‐MS analyses suggest that one IAP ligand dissociated from [Ni(IAP)2] to generate the Ni–enolate of 3′‐indolyl‐3‐oxindole. From the optically active 3, 3′‐mixed indole adduct, biologically important 3′‐indolyl‐3‐pyrrolidinoindoline was successfully synthesized in a three‐step reaction sequence.